Theoretical and experimental implementation of PID and sliding mode control on an inverted pendulum system - K. Dawane, Mahendra; M. Malwatkar, Gajanan (Bulletin of Electrical Engineering and Informatics, 2025)
This paper explores the theoretical and experimental implementation of proportional-integral-derivative (PID) and sliding mode control (SMC) on an inverted pendulum system, a well-known problem in control engineering that is inherently unstable and highly nonlinear. The primary objective of this study is to evaluate and compare the effectiveness of these two control strategies in achieving system stabilization and robustness against disturbances. The PID controller, widely utilized due to its straightforward design and implementation, is developed based on the linearized model of the inverted pendulum. On the other hand, the SMC technique, known for its robustness to system uncertainties and external disturbances, is employed to tackle the nonlinear nature of the system. The controllers are tested in both simulation and real-time experimental environments to ensure the reliability of the findings. The results from the experiments indicate that while the PID controller performs adequately under nominal conditions, it struggles to maintain stability when faced with parameter variations and external perturbations. In contrast, the SMC exhibits superior performance by consistently stabilizing the pendulum even under adverse conditions, demonstrating its robustness and effectiveness in managing nonlinear systems. This comparative analysis provides valuable insights into the practical applications of PID and SMC, highlighting the trade-offs between simplicity and robustness in control system design.